2014
DOI: 10.1155/2014/132950
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Tilt Angle for Photovoltaic Solar Panels in Zomba District, Malawi

Abstract: A study to determine the optimum tilt angle for installing photovoltaic solar panels in Zomba district, Malawi, has been conducted. The study determined the optimum monthly tilt angles of PV solar panels and the seasonal adjustments needed for the panels in order to collect maximum solar radiation throughout the year. In this study, global solar radiation (GSR) on four tilted surfaces was measured. The north-facing surfaces were titled at angles of 0°, 15°, 20°, and 25°. The GSR data was used to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
3
0
4
Order By: Relevance
“…Sonuç olarak panellerin, güney yönünde 25 derece açıyla yerleştirildiğinde en yüksek ışınım değerini elde edeceği sonucuna varmışlardır. Ek olarak şekilde 0 ile 25 derece açıların saat 12 civarında değerleri karşılaştırıldığında %20 verim artışı elde etmişlerdir [3].…”
Section: Optimum Açıunclassified
See 3 more Smart Citations
“…Sonuç olarak panellerin, güney yönünde 25 derece açıyla yerleştirildiğinde en yüksek ışınım değerini elde edeceği sonucuna varmışlardır. Ek olarak şekilde 0 ile 25 derece açıların saat 12 civarında değerleri karşılaştırıldığında %20 verim artışı elde etmişlerdir [3].…”
Section: Optimum Açıunclassified
“…Zamana bağlı ışınım grafiği [3] Buna ek olarak her 1 C sıcaklık farkında enerjide dönüşümünde %0.4-0.5 arasında kayıp olmaktadır [9]. Sonuç olarak sıcaklığın verim ile ilişkisi panel verimliliği açısından önemlidir.…”
Section: çAlışma Sıcaklığıunclassified
See 2 more Smart Citations
“…Ng et al (2014) found that the optimum angles for seasonal south-and north-facing surfaces are 14.4° and 14.8°, respectively. Kamanga et al (2014) mentioned that for Zomba district there are only two seasonal adjustments that are needed for PV solar panels and these should be carried out at the end of February and at the end of September. For fixed solar panels with no seasonal adjustments, the optimum tilt angle for the PV solar panels that are north facing has been determined to be 25°.…”
Section: Introductionmentioning
confidence: 99%